Exploring Charismatic Leadership and Personality Competence: Keys to Fostering Teacher Motivation: English - Basri, Hasan; Manshur, Umar; Baharun, Hasan; Zaini, Abdul Wahid; Suhermanto, Suhermanto (Bidayatuna, 2024)
This research focuses on understanding the impact of charismatic leadership, personality competencies, working environment conditions, social support, and work-life balance on teachers' work motivation in various educational institutions. This study aims to explore in depth the influence of charismatic leadership and personality competence on their work motivation in Madrasah Ibtidaiyah (MI) Hasanuddin. The research method used is a quantitative survey study through questionnaires distributed to teachers in various educational institutions, using regression analysis to identify the relationship between independent variables (such as charismatic leadership and personality competence) and dependent variables (teacher work motivation). The results of this study show a significant influence of Charismatic Leadership and Personality competence on Teacher Work Motivation in MI Hasanuddin. Descriptive analysis found a high level of charismatic leadership, personality competence, and teacher work motivation. Linear regression analysis corroborates these findings by showing that both factors significantly affect teacher work motivation; in particular, charismatic leadership contributes more than personality competence. The implications of this study show that Charismatic Leadership and Personality competencies significantly influence teacher work motivation, highlighting the importance of the role of leadership and personal development of teachers in creating a motivating work environment.